LAND.TECHNIK 2020: The Forum for Agricultural Engineering Innovations - VDI Wissensforum GmbH (VDI Verlag, 2020)
Electrical SystemsSustainable Agriculture in an Electrifed World – Cradle-to-Grave evaluation of diﬀerent propulsion systems 1Understanding the opportunities and challenges of self-driving, electric feld tractors using dynamic discrete-event simulation 9Design and analysis of a magnetic-electrical power split gearbox for application in an agricultural vehicle   17Development of a 3-speed gearbox in electric powertrain – Ground drive transmission for a commercial vehicle   23Data ManagementFarmers’ expectations in Precision Farming Technologies – Transfarm 40 online survey 2019 31Cyber Threats and Cyber Risks in Smart Farming  37Automatic logging and situation-related evaluation of manufacturer independent machine data  47Data insight and expert knowledge combined to maximize uptime   55…...